El Clima Organizacional y su Influencia en el Desarrollo de Liderazgo de los Oficiales del Ejército Peruano en el 2011 - Canario Quiroz, Ilaire Manfredi (2013)
The present research work for the War College [ESGE], aims to raise awareness of the importance of these two components as features inherent in all military personnel within the institution and its impact on it. It describes the relationship between organizational climate and military leadership. We discuss the importance of moral values within this institution. It identifies the types of values and predominantly practiced the kind of leadership that currently prevails In research for purposes of this thesis, in addition to developing the conceptual framework and provide data of actors committed to the issue in question. Moreover, the empirical evidence is based on fieldwork, with the support of different data collection instruments including a questionnaire, semi-structured interview which allowed us to gather information on the issue. We performed a non-experimental and use a crossover design with a single measurement that is scaled to the participants of the 2011 course ESGE, who by their experience are able to answer objectively. The variables taken into account are the first, the organizational climate and the second: Military Officer Leadership. It was found that the organizational climate and leadership are related aspects and we will take steps to leadership is driving on the right path of discipline and respect. It determines how the organizational climate indicators affect the kind of leadership in the EP and predominantly practiced in the ESGE The type of leadership that currently prevails in the institution is strong in its foundations, however, a factor to consider is the organizational climate Finally it explains why you should look for an organizational climate that meets the needs of our institution so that decision-making process is adequate for the exercise of leadership. Keywords: Organizational Climate, Leadership, Values Warlord. Organizational culture